The implementation of Importance Performance Analysis (IPA) to determine the quality of service towards the tourists’ expectations of Al-Fatih tour & travel - Alwin Lasarudin; Pradnya Paramita Yoanda (Universitas Merdeka Malang, 2024)
Improving service quality to meet diverse tourist expectations. Importance-Performance Analysis (IPA) is an effective method for evaluating and enhancing service quality. Significant transformations in the tourism industry involve global mobility, technology, and changing customer preferences. Tourists now expect friendly personal interactions, fast service, and experiences tailored to their needs. Holistic and structured assessments are required to identify areas needing improvement and to allocate resources effectively. IPA helps BPW management set priorities and improvement strategies based on the differences between the importance and performance of service elements. This study aims to implement IPA in evaluating services at Al-Fatih Tour & Travel, highlighting nine priority services that need enhancement to meet tourists' expectations. The results using the IPA Cartesian diagram show nine priority services to be improved in quality: (1) Environmental conditions, (2) Appearance, (3) Accuracy in fulfilling promises, (4) Booking and delivery services, (5) Fast and accurate service, (6) Readiness to provide service, (7) Providing a sense of security, (8) Knowledge and skills according to their field, (9) Treating tourists with full attention.